The Effect of Islamic Spiritual Activities and Islamic Education Teachers’ Role Modeling on The Religious Character of Tenth-Grade Students at SMAN 5 Berau - Rani Selfiana; Benny Prasetya; Muhammad Alfi Syahrin; Khamam Khosiin (PT. Caesarindo Triloka Persada, 2026)
This study is motivated by the importance of forming students’ religious character in senior high schools as part of national education goals, as well as the existing gap between religious understanding and its implementation in daily life. This study aims to examine the effect of Islamic Spiritual Activities (Rohani Islam) and the role modeling of Islamic Education teachers on the religious character of tenth-grade students at SMAN 5 Berau, both partially and simultaneously. This research employed a quantitative approach with a correlational research design. The population consisted of all tenth-grade students of SMAN 5 Berau, with a sample of 82 students selected using random sampling techniques. Data were collected through Likert-scale questionnaires, observation, and documentation. Data analysis was conducted using multiple linear regression analysis. The results indicate that Islamic Spiritual Activities have a significant effect on students’ religious character, Islamic Education teachers’ role modeling has a significant effect on students’ religious character, and both variables simultaneously have a significant influence on students’ religious character. This study concludes that strengthening school-based religious activities supported by exemplary behavior from Islamic Education teachers is an effective strategy for developing students’ religious character in public high schools.